Pendekatan Implementasi Model Substractive Clustering Dalam Memetakan Dan Klasifikasi Data Perilaku Konsumen Listrik Tegangan Rendah Studi Kasus : Pelanggan PT PLN (Persero) UP3 Cengkareng - Yozika Arvio; Iriansyah BM Sangadji; Hengki Sikumbang; Meilinda Devi Anjarwati (PETIR, 2019)
Electrical energy is one of the most important and vital human needs that cannot be released from daily needs. Customers also have begun to be critical of the purchase costs that must be paid every month. So by increasing electricity rates, improving efficiency in the use of electric power is a major consideration. The Advanced Measurement Infrastructure System (AMI) provides information on the use of granular energy for needs and customers. The IT system at AMI one of which uses EMS (Energy Management System) is an application to collect data from every smart meter installed in the customer, to store it in a database, and to connect the analysis and statistics of the data stored below. In this study aims to provide an analysis of electricity usage patterns by implementing AMI / Smart meters PT. PLN (Persero) by conducting a cluster of 1 phase and 3 phase electricity usage in customers of PT PLN (Persero) UP3 Cengkareng, namely the distribution booths DK60, TG70 and DK242 for 4 months, from November 2018 to February 2019. From the results of the study sought for customers 1 phase DK 60 with a radius of 0.5 produces 1 cluster that is stable every month depending on the customer at this substation is a household class customer, TG 70 requires stable and spending usage in December 2018, and DK 242 fix stable and use customers in the month December 2018 and January 2019, while for 3-phase DK 60 customers tend to be unstable because the customers of this apartment are different, starting from shops, production sites, and CV. TG 70 substations are predominantly places of worship, namely mosques and mosques, so the average use of mosques is higher, and for DK 242 3-phase customers need to be stable and use the highest in January 2019.AMI, System, EMS, Distribution Substation, Phase.